Thai Food Recommendation System using Hybrid of Particle Swarm Optimization and K-Means Algorithm - Tanakorn Puraram; Pimwadee Chaovalit; Apatha Peethong; PONGSAK TIYANUNTI; Supiya Charoensiriwath; Warangkhana Kimpan (My University, 2021)
A food recommendation system is an information filtering tool that helps suggest appropriate food menus to users based on their dietary behavior, nutrition, health, or activity. In this paper, a hybrid method of Particle Swarm Optimization (PSO) and K-Means algorithm is proposed to improve the user's dietary behavior clustering and using Principal Component Analysis (PCA) to reduce the data dimension. Moreover, the User-Based Collaborative Filtering technique is used to predict the rating of relevant Thai food menus and recommendation. The experimental result shows the hybrid method improves the clustering performance from 3 models: Hierarchical Clustering, K-Means, and K-Means with PCA, in terms of silhouette coefficient score. In addition, the hybrid method improves the Davies-Bouldin index score by 44%, 19%, and 17% compared to those models, respectively. The rating prediction result shows the hybrid method outperforms the other methods.
Keywords: Recommender Systems and Techniques; Customer churn and segmentation; Human Mobility and Location-Based Analysis